Carbamoyl Fluorides: A Platform to Interrogate Fluoride-Enabled Reactivity - Jabbarpoor, Maryam; Le, Christine M. (Synthesis, 2025)
The strong and polar nature of C–F bonds impart organofluorine compounds with highly desirable properties, making them indispensable in pharmaceutical, agrochemical, and polymer research. While this bond strength makes the modification of organofluorine compounds challenging, it also creates opportunities for the development of innovative strategies for their functionalization. Carbamoyl fluorides represent an emerging class of fluorinated electrophiles, showcasing unique fluoride-enabled reactivity and serving as versatile building blocks for accessing valuable amides and heterocyclic compounds. This review highlights recent progress in the synthesis and reactivity of carbamoyl fluorides, including comparisons to their chlorinated counterparts where relevant.1 Introduction2 Synthesis and Simple Nucleophilic Substitution Reactions of Carbamoyl Fluorides2.1 Direct Use of Difluorophosgene2.2 Use of (Di)fluorophosgene Equivalents2.2.1 From Isocyanates and Thioformamides2.2.2 From Amines2.3 Use of Difluorocarbene Sources2.4 Use of CO2 and Deoxyfluorinating Reagents2.5 Miscellaneous Methods3 Reactivity of Carbamoyl Fluorides3.1 Covalent Inhibition of Enzymes3.2 Nucleophilic Substitution3.3 Transition-Metal-Catalyzed C–F Bond Activation3.4 Lewis Acid and Base Catalyzed Carbamoylation4.0 Outlook and Conclusion
Keywords: fluorine; carbamoyl fluoride; fluoride-enabled reactivity; carbamoylation; C–F bond functionalization; difluorocarbene; fluorophosgene